Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Savi Pada Perkalian Di Kelas Iii Sdn 064974 Medan Tembung Tahun Pembelajaran 2024/2025 - Naibaho, Sisilia Hotrepiyanti Br; Arifin, Muhammad; Gunawan, Erli (Jurnal Ilmiah Wahana Pendidikan, 2025)
This writing aims to improve student learning outcomes by using the SAVI multiplication learning model in class III at SDN 064974 Medan Tembung for the 2024/2025 academic year. This type of writing is class action writing (PTK). The subjects of this writing are class III students at SDN 064974 Medan Tembung. Based on the writing results obtained, there was an increase in student learning outcomes in multiplication material in class III at SDN 064974 Medan Tembung for the 2024/2025 academic year. The writing results in the first cycle of students who got a complete score were 12 students or 44% while the students who did not complete were 15 students or 56% with an average score of 64. In the second cycle of students who got a complete score there were 25 students or 93% while the 2 students or 7% did not complete with an average score of 80. The increase in learning outcomes occurred after improvements in actions in cycle II. The action was stopped in cycle II because it had reached the success criteria, thus it was concluded that by using the SAVI learning model student learning outcomes increased in Multiplication in Class III SDN 064974 Medan Tembung.